RECOMMENDATIONS RELATED TO ADVISORY PANEL - CHILCOTE SD (Tufts Archival Research Center, 2007)
Missing Attachments; Memorandum from Peter Sparber to Karen Fernicola Shur regarding a fire safety advisory panel. Identifies the objective as promoting fire safety education programming, particularly by highlighting work the tobacco industry has done. Presents criteria for selecting members and recommends individuals.